Determination of Alterations in Protein Profiles of Brain Tissues of Experimental Epilepsy Models by Proteome Analysis - Danis, O.; Demir, S.; Aker, R.; Gunel, A.; Onat, F.; Ogan, A. (Blackwell Publishing, 2006)
…
31st Congress of the Federation-of-European-Biochemical-Societies (FEBS) -- JUN 24-29, 2006 -- Istanbul, TURKEY